Curriculum Development Effectiveness And Classroom Management: The Mediating Role of Learning Motivation and Its Implication to Academic Achievement in Madrasah Ibtidaiyah - Siti Nur Aisyah; Fiqqi Syumaya Hakim; Enas Enas; Asep Saepul Hidayat (Balai Diklat Keagamaan Bandung, 2026)
This study examines the effects of curriculum development effectiveness and classroom management on students’ learning motivation and academic achievement in Madrasah Ibtidaiyah in Sumedang Regency, Indonesia. A quantitative approach was employed using an explanatory survey and an ex post facto design. The study involved all 64 Madrasah Ibtidaiyah in the regency, selected through a total sampling technique. Data were collected through teacher questionnaires and supported by students’ National Assessment results. The data were analyzed using descriptive statistics, multiple regression, and path analysis. The findings indicate that both curriculum development effectiveness and classroom management have positive and significant effects on students’ learning motivation. Learning motivation, in turn, exerts a significant positive effect on academic achievement. Furthermore, the results demonstrate that learning motivation mediates the relationship between curriculum development effectiveness, classroom management, and academic achievement. These findings suggest that improving curriculum implementation and fostering conducive classroom environments can strengthen students’ motivation and contribute to better academic outcomes. The study concludes that improving academic achievement in Madrasah Ibtidaiyah requires integrated efforts involving effective curriculum development, supportive classroom management, and continuous reinforcement of students’ learning motivation.